2016
DOI: 10.3390/ijms17040590
|View full text |Cite
|
Sign up to set email alerts
|

Matrilin-3 Role in Cartilage Development and Osteoarthritis

Abstract: The extracellular matrix (ECM) of cartilage performs essential functions in differentiation and chondroprogenitor cell maintenance during development and regeneration. Here, we discuss the vital role of matrilin-3, an ECM protein involved in cartilage development and potential osteoarthritis pathomechanisms. As an adaptor protein, matrilin-3 binds to collagen IX to form a filamentous network around cells. Matrilin-3 is an essential component during cartilage development and ossification. In addition, it intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…These include aggrecan, a large chondroitin sulphate proteoglycan that helps retain water in the cartilage due to its high negative ionic charge. 10 Matrillins help hold aggrecan clumps in place, 11 whereas perlecan, a large heparin sulphate/chondroitin sulphate complex, helps provide structural strength and promotes angiogenesis. 12 Cartilage oligomeric matrix protein, also known as COMP5 or thrombospondin5, provides homeostatic support for the chondrocytes themselves and catalyses the polymerization of type II collagen.…”
Section: Structural Compositionmentioning
confidence: 99%
“…These include aggrecan, a large chondroitin sulphate proteoglycan that helps retain water in the cartilage due to its high negative ionic charge. 10 Matrillins help hold aggrecan clumps in place, 11 whereas perlecan, a large heparin sulphate/chondroitin sulphate complex, helps provide structural strength and promotes angiogenesis. 12 Cartilage oligomeric matrix protein, also known as COMP5 or thrombospondin5, provides homeostatic support for the chondrocytes themselves and catalyses the polymerization of type II collagen.…”
Section: Structural Compositionmentioning
confidence: 99%
“…The results of several recent studies suggest that combining MSCs with chemical agents or platelet lysates yields articular cartilage with improved quality (Bornes et al, 2014;Filardo et al, 2013;Lee et al, 2014). Besides chemical agents or platelet lysates, matrilin-3 is considered a potential molecule for codelivery with MSCs (Muttigi, Han, Park, Park, & Lee, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In primary human chondrocytes, MATN3 can induce the expression of MMP1, MMP3, MMP13, and COX2, indicating that MATN3 can regulate extracellular matrix degradation [12]. Existing data [13,14] provide insights into the critical role of matrilin-3 in in ammation, matrix degradation, and matrix formation in cartilage development and osteoarthritis. So far, although many studies about MATN3 have been limited to epiphyseal disease, few studies have been reported on other conditions such as malignant tumors.…”
Section: Discussionmentioning
confidence: 99%